2012
DOI: 10.1186/1472-6890-12-14
|View full text |Cite
|
Sign up to set email alerts
|

Tenascin-W is a better cancer biomarker than tenascin-C for most human solid tumors

Abstract: BackgroundTenascins are large glycoproteins found in the extracellular matrix of many embryonic and adult tissues. Tenascin-C is a well-studied biomarker known for its high overexpression in the stroma of most solid cancers. Tenascin-W, the least studied member of the family, is highly expressed in the stroma of colon and breast tumors and in gliomas, but not in the corresponding normal tissues. Other solid tumors have not been analyzed. The present study was undertaken to determine whether tenascin-W could se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 33 publications
(52 reference statements)
0
43
0
Order By: Relevance
“…Tenascin-W is the most recently characterized member of the tenascin gene family. Similar to tenascin-C, it is found in the stroma of many solid tumors (Brellier et al, 2012a). Tenascin-W is also expressed in developing and adult trabecular bone, and it promotes the migration and proliferation of osteoblasts in vitro (Meloty-Kapella et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Tenascin-W is the most recently characterized member of the tenascin gene family. Similar to tenascin-C, it is found in the stroma of many solid tumors (Brellier et al, 2012a). Tenascin-W is also expressed in developing and adult trabecular bone, and it promotes the migration and proliferation of osteoblasts in vitro (Meloty-Kapella et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, tenascin-W exhibits an even more restricted expression pattern in normal tissues than tenascin-C and has been proposed as a superior biomarker for malignancy. 150 Therapeutic exploitation of tenascin-C splice variants The strong association between the expression of alternatively spliced FNIII repeats of tenascin-C with tumors, and in many cases very aggressive tumors, combined with their reduced expression in normal healthy tissues has raised interest in pharmacological targeting of these modules. These studies are extensively reviewed in, 3 and are therefore only summarized below.…”
mentioning
confidence: 99%
“…Although tenascin is known to be produced by mesenchymal cells, recent studies have shown that epithelial cells also contribute to its production (8). According to Regezi et al (22), tenascin is localized at the epithelial-connective tissue interface and is expressed by both mesenchymal cells and keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Still, the relationship between MMP and tenascin expression and the biological behavior of odontogenic lesions has not yet been identified. Based on the facts that MMPs are implicated in tumor progression (7) together with local invasiveness and that tenascin has been suggested to affect epithelial-mesenchymal interactions in some tumors (8), the purpose of our study was to evaluate MMP-I, -9 and tenascin expression in ABLs and KOTs by immunohistochemical assessment. The expression patterns of MMP-I, -9 and tenascin in these lesions are hypothesized to be associated with their local aggressive behavior.…”
Section: Ameloblastomamentioning
confidence: 99%